SAGE II observations of polar stratospheric clouds near 50 deg N January 31 - February 2, 1989 - Pitts, M. C.; Poole, L. R.; Mccormick, M. P. (1990)
Polar stratospheric clouds (PSCs) form at very cold temperatures which typically occur only at high latitudes during local winter. However, meteorological circumstances in the Arctic during late January 1989 led to PSC formation unusually far to the south, at latitudes (near 50 deg N) being sampled during the period by the orbiting SAGE II instrument. These unusual PSC sightings and the evolution of meteorological conditions which produced the episode are described. Profiles of SAGE II extinction measurements at 0.525 and 1.02 microns show clear signatures of PSCs and indicate that the cloud particles were considerably larger than the background aerosol. It is most important to note that the clouds were sighted at a latitude where there was extensive sunlight, thus increasing the likelihood of ozone loss both locally and downstream due to enhancements in reactive chlorine expected from heterogeneous chemical processing within the PSCs.